Effect of processing on bioaccessibility of carotenoids from orange maize products. (19th April 2021) - Song, Yuwei; Ndolo, Victoria; Fu, Bin Xiao; Ames, Nancy; Katundu, Mangani; Beta, Trust
Summary: This study assessed the effect of processing including boiling, roasting and fermenting on bioaccessibility of carotenoids (lutein, zeaxanthin, β‐cryptoxanthin, α‐carotene and β‐carotene) from orange maize. Bioaccessibility of carotenoids was analysed using a three‐stage in vitro digestion. High‐performance liquid chromatography was used to analyse the contents of carotenoid compounds in the processed orange maize products and digesta. On average, boiled maize had the highest retention rate (79.0%) of carotenoids followed by fermented porridge (73.8%), fermented maize (68.4%) and unfermented porridge (59.0%). Roasted maize had the lowest retention rate of 56.1%. Without further processing, carotenoids recovery from raw orange maize ranged from 73.0% to 100.5%. After treatments, carotenoids recovery showed varying levels of increase except for fermented maize. The average recovery of carotenoids in whole digesta of boiled maize, roasted maize, fermented porridge and unfermented porridge was 108.5%, 116.9%, 101.9% and 110.7%, respectively. Abstract : Processing affects bioaccessibility of maize carotenoids; however, simply boiling retains the most in intact grains.